Effectiveness of haloperidol prophylaxis in critically ill patients with a high risk of delirium: a systematic review. (May 2017) - Santos, Eduardo; Cardoso, Daniela; Neves, Hugo; Cunha, Madalena; Rodrigues, Manuel; Apóstolo, João
EXECUTIVE SUMMARY: Background: Delirium is associated with increased intensive care unit and hospital length of stay, prolonged duration of mechanical ventilation, unplanned removal of tubes and catheters, and increased morbidity and mortality. Prophylactic treatment with low-dose haloperidol may have beneficial effects for critically ill patients with a high risk of delirium. Objectives: To identify the effectiveness of haloperidol prophylaxis in critically ill patients with a high risk for delirium. Inclusion criteria Types of participants : Patients with a predicted high risk of delirium, aged 18 years or over, and in intensive care units. Patients with a history of concurrent antipsychotic medication use were excluded. Types of intervention(s)/phenomena of interest : Haloperidol prophylaxis for preventing delirium. Types of studies : Experimental and epidemiological study designs. Outcomes: Primary outcome is the incidence of delirium. Secondary outcomes are duration of mechanical ventilation, incidence of re-intubation, incidence of unplanned/accidental removal of tubes/lines and catheters, intensive care unit and hospital length of stay, and re-admissions to both settings. Search strategy: An initial search of MEDLINE and CINAHL was undertaken, followed by a second search for published and unpublished studies from January 1967 to September 2015 in major healthcare-related electronic databases. Studies in English, Spanish and Portuguese were included. Methodological quality: Two independent reviewers assessed the methodological quality of five studies using the standardized critical appraisal instrument from the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument. There was general agreement among the reviewers to exclude one relevant study due to methodological quality. Data extraction: Data were extracted using the JBI data extraction form for experimental studies and included details about the interventions, populations, study methods and outcomes of significance to the review questions. Data synthesis: Significant differences were found between participants, interventions, outcome measures (clinical heterogeneity) and designs (methodological heterogeneity). For these reasons, we were unable to perform a meta-analysis. Therefore, the results have been described in a narrative format. Results: Five studies met the inclusion criteria. One of these studies was excluded due to poor methodological quality. The remaining four original studies (total of 1142 patients) were included in this review. Three studies were randomized controlled trials and one was a cohort study. Two studies confirmed the effectiveness of haloperidol prophylaxis in critically ill patients with a high risk of delirium. These studies showed that short-term prophylactic administration of low-dose intravenous haloperidol significantly decreased the incidence of delirium in elderly patients admitted to intensive care units after non-cardiac surgery and in general intensive care unit patients with a high risk of delirium. However, the two remaining studies showed contradictory results in mechanically ventilated critically ill adults, revealing that the administration of haloperidol reduced delirium prevalence, delayed its occurrence, and/or shorten its duration. Conclusions: The evidence related to the effectiveness of haloperidol prophylaxis in critically ill patients with a high risk of delirium is contradictory. However, balancing the benefits and low side effects associated with haloperidol prophylaxis, this preventive intervention may be useful to reduce the incidence of delirium in critically ill adults in intensive care units.